Stem Cell Therapy on the Internet: Information Quality and Content Analysis of English Language Web Pages Returned by Google - Meehan, Douglas; Bizzi, Isabella Harb; Ghezzi, Pietro (Frontiers in ICT, 2017)
There are expectations that stem cell therapy (SCT) will treat many currently untreatable diseases. The Internet is widely used by patients seeking information about new treatments, and hence, analyzing websites is a representative sample of the information available to the public. Our aim was to understand what information the public would find when searching for information on SCT on Google, as this would inform us on how lay people form their knowledge about SCT. We analyzed the content and information quality of the first 200 websites returned by a Google.com search on SCT. Most websites returned were from treatment centers (TC, 44%) followed by news and medical professional websites. The specialty most mentioned in non-TC websites was “neurological” (67%), followed by “cardiovascular” (42%), while the most frequent indication for which SCT is offered by TCs was musculoskeletal (89%) followed by neurological (47%). 45% of the centers specialized in treating one specialty, 10% two and 45% offered between three and 18 different specialties. Of the 78 treatment centers, 65% were in the USA, 23% in Asia and 8% in Latin America. None of the centers offered SCT based on embryonic cells. Health information quality (JAMA score, measuring trustworthiness) was lowest for TCs and commercial websites and highest for scientific journals and health portals. This study shows a disconnection between information about SCT and what is actually offered by TCs. The study also shows that TCs, potentially acting in a regulatory grey area, have a high visibility on the Internet.